Redescription of Argizala brasiliensis Walker, 1869 (Orthoptera: Grylloidea: Trigonidiidae: Nemobiinae: Pteronemobiini) and consideration of its morphological proximity to other Pteronemobiini Nearctic genera - Pereira, Marcelo Ribeiro; Martins, Luciano De P.; Fernandes, Maria Luiza; Zefa, Edison; Sperber, Carlos Frankl (Zootaxa, 2015)
Although male crickets provide more informative characters for the delimitation of species and genera, many taxonomic descriptions are based only on females. This is the case for Argizala Walker, 1869 and its two valid species, A. brasiliensis Walker, 1869 and A. hebardi Rehn, 1915. We provide herein a redescription of A. brasiliensis based on a male collected in the Pampa Biome, Capão do Leão municipality, Rio Grande do Sul State, Brazil. We present photographs of epitype and male genitalia, and discuss the diagnostic features of the genus and its morphological proximity to other Pteronemobiini Nearctic genera.